(3GdJHjf Ydi efGd Gdjbjfs - (3efPQ Hf SYjO GdHdhWis ((3eMehO Hf CMeO Hf GHQGgje GdaGQSi s)
(3ChdgG (B:s
(3GdMeO ddg GdMejO GdeLjO GdeHJOF GdeYjO QCjJ hVY gPG GdcJGH CHJZi ef Gddg MSf GdLRGA eG hUaJ ef GdGghGd heKdK ajg ef ehGba jhe GdMSGH s
(3BNQgG (B:s
(3hge jfXQhf Edi GdedGFcI MGajf ef Mhd GdYQV jSHMhf HMeO QHge hbVi Hjfge HGdMb hbjd GdMeO ddg QH GdYGdejf hCNQLfG ef Xde GdLgGdI hCONGdfG Hg ai NjQ CeI hYdi Bdg hSde Je cJGH GdJHjjf HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs